2023
DOI: 10.3390/insects14010089
|View full text |Cite
|
Sign up to set email alerts
|

Insect Freeze-Tolerance Downunder: The Microbial Connection

Abstract: Insects that are freeze-tolerant start freezing at high sub-zero temperatures and produce small ice crystals. They do this using ice-nucleating agents that facilitate intercellular ice growth and prevent formation of large crystals where they can damage tissues. In Aotearoa/New Zealand the majority of cold adapted invertebrates studied survive freezing at any time of year, with ice formation beginning in the rich microbiome of the gut. Some freeze-tolerant insects are known to host symbiotic bacteria and/or fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 105 publications
0
1
0
4
Order By: Relevance
“…Pioneer studies revealed that microorganisms themselves ( 60 , 61 ) by acting as surfaces for the promotion of water molecule aggregation ( 62 ) may confer resistance to subzero temperatures ( 63 ). Other investigations on aquatic and terrestrial poikilothermic organisms hypothesized a connection between freeze tolerance and microbiome ( 64 , 65 ). However, information on the role of the microbiome in the mechanisms adopted by marine invertebrates to cope with extreme cold and freezing conditions is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneer studies revealed that microorganisms themselves ( 60 , 61 ) by acting as surfaces for the promotion of water molecule aggregation ( 62 ) may confer resistance to subzero temperatures ( 63 ). Other investigations on aquatic and terrestrial poikilothermic organisms hypothesized a connection between freeze tolerance and microbiome ( 64 , 65 ). However, information on the role of the microbiome in the mechanisms adopted by marine invertebrates to cope with extreme cold and freezing conditions is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Otros factores que afectan el MBI son el estado nutricional del huésped, la estación del año, la inoculación de la descendencia Las bacterias intestinales mejoran la digestión de los alimentos al descomponer la celulosa y aumentar la absorción de nutrientes, lo que incrementa la gama de fuentes de alimentos y las tasas de crecimiento de los huéspedes (Morgan-Richards et al, 2023). La mediación entre insectos y microorganismos es crítica en la descomposición de la biomasa vegetal y el ciclo del carbono, así como en las tasas de fijación de nitrógeno (Engel y Moran, 2013).…”
Section: Factores Que Modifican El Microbioma En Los Insectosunclassified
“…La mediación entre insectos y microorganismos es crítica en la descomposición de la biomasa vegetal y el ciclo del carbono, así como en las tasas de fijación de nitrógeno (Engel y Moran, 2013). Además, están involucrados en el almacenamiento de grasa, la producción de aminoácidos esenciales y la protección contra patógenos, lo que mejora la respuesta inmune del huésped (Gurung et al, 2019;Morgan et al, 2023). Las bacterias también contribuyen a la comunicación entre miembros de esta y de distintas especies, brindan protección contra enemigos naturales y gobiernan los sistemas reproductivos y de apareamiento (Engel y Moran, 2013).…”
Section: Factores Que Modifican El Microbioma En Los Insectosunclassified
See 2 more Smart Citations